Stem Cell Therapeutics in veterinary medicine in India - Gugjoo, Mudasir Bashir; Farooq, Fajar; Sakeena, Qumaila; Dar, Ejaz Rasool; Khan, Sharun; Amarpal, Amarpal; Parrah, Jalal ud Din; Makhdoomi, Dil Mohammad; Dhama, Kuldeep; Sharma, Gutulla Taru (The Indian Journal of Animal Sciences, 2022)
Stem cell, a wonder cell, acts as a basic unit for an individual development in early prenatal life, andrepairs and regenerates the tissue and/ organ in post-natal life. The stem cell research although conducted extensively is still in its infancy for standardized therapeutics. Among various stem cells types, multi-potential mesenchymal stem cell (MSC) is mainly evaluated for therapeutic applications. These cells have been isolated from almost all the body organs/ tissues and fetal membranes and are culture expanded for higher concentrations. Like human, MSCs harvested from veterinary species are characterized on the basis of International Society for Cellular Therapy (ISCT). Extensive literature on their therapeutic applications in musculoskeletal and non-musculoskeletal systems evidences their potential utility under clinical settings. Currently, limited understanding in their  hysiological mechanisms and availability of limited non-uniform in vivo studies restrict their definitive therapeutic applications. Lack of regulatory set up in India makes MSCs research in veterinary medicine a more complicated field. This review details the current status and possible ways to improve MSCs therapeutic applications in veterinary medicine, in  general and in Indian system, in particular.